Identification and Integration of Career Theory: Students' Perspectives on the Process. Issue 1 (8th March 2019) - Lindo, Natalya A.; Cartwright, Angie D.; Ceballos, Peggy; Conner, Charmaine; Edwards, Josh; Blalock, Sarah
Abstract : In many counseling programs, while students are learning about career theory, they may be tasked in a separate course with identifying a theoretical approach to counseling. This may result in a dichotomous situation in which students lack an understanding of the relationship between career theory and counseling theory. Career counselors have long recognized the artificial distinction between career counseling and general counseling. However, counselor education programs generally lag, and there is a dearth of literature regarding the process of identifying and integrating career theory and counseling theory. This phenomenological study examined 6 students' perceptions of the process of career theory identification and integration. Analysis of in‐depth interviews yielded 5 major themes: theory identification and integration, perceptions of career counseling, resources, personal dimensions, and application across the life span. Findings of this study have the potential to inform counselor education pedagogy regarding career theory identification and its application to the counseling context.